Implementation of The Islamic Legal Maxim Al-Umūru bi Maqāṣidihā in Islamic Education Curriculum Planning - Fajar Alfaris; Hermawan; Andy Fahmi Halim; Fikry Firmansyah (Ambarsa : Jurnal Pendidikan Islam, 2026)
This study aims to analyze the implementation of the Islamic legal maxim al-umūru bi maqāṣidihā in the curriculum planning of Islamic education at Pondok Pesantren Imam Muslim Al-Atsary Kediri. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving pesantren leaders, curriculum administrators, and teachers. The findings reveal that the curriculum planning process is systematically oriented toward maqāṣid-based educational objectives, particularly in shaping Islamic character, strengthening religious understanding, and developing students’ da‘wah orientation. The implementation of the maxim is reflected in the determination of learning objectives, selection of curriculum materials, structuring of educational levels, and formulation of student achievement targets aligned with Islamic values. The study also identifies a strong integration between formal curriculum and hidden curriculum through habituation, discipline, and pesantren culture as media for value internalization. Theoretically, this research contributes to the development of Islamic Education Management by strengthening curriculum planning frameworks based on qawāʿid fiqhiyyah and maqāṣid al-sharī‘ah. Practically, the findings suggest that Islamic educational institutions should position goal orientation as the primary foundation in curriculum development to ensure coherent, value-based, and holistic educational outcomes.